Microbiota and Other Preventive Strategies and Non-genetic Risk Factors in Parkinson’s Disease - Franco, Rafael; Rivas-Santisteban, Rafael; Reyes-Resina, Irene; Navarro, Gemma; Martínez-Pinilla, Eva (Frontiers in Aging Neuroscience, 2020)
The exact cause of Parkinson’s disease (PD), the second most prevalent neurodegenerative disease in modern societies, is still unknown. Many scientists point out that PD is caused by a complex interaction between different factors. Although the main risk factor is age, there are other influences, genetic and environmental, that individually or in combination may trigger neurodegenerative changes leading to PD. Nowadays, research remains focused on better understanding which environmental factors are related to the risk of developing PD and why. In line with the knowledge on evidence on exposures that prevent/delay PD onset or that impact on disease progression, the aims of this review were: (i) to comment on the non-genetic risk factors that mainly affect idiopathic PD; and (ii) to comment on seemingly reliable preventive interventions. We discuss both environmental factors that may affect the central nervous system (CNS) or the intestinal tract, and the likely mechanisms underlying noxious or protective actions. Knowledge on risk, protective factors, and mechanisms may help to envisage why nigral dopaminergic neurons are so vulnerable in PD and, eventually, to design new strategies for PD prevention and/or anti-PD therapy. This article reviews the variety of the known and suspected environmental factors, such as lifestyle, gut microbiota or pesticide exposition, and distinguishes between those that are harmful or beneficial for the PD acquisition or progression. In fact, the review covers one of the most novel players in the whole picture, and we address the role of microbiota on keeping a healthy CNS and/or on preventing the “side-effects” related to aging.